2022
DOI: 10.2147/ppa.s390596
|View full text |Cite
|
Sign up to set email alerts
|

Illness Beliefs, Treatment Beliefs, and Fulfilled Treatment Expectations in Psychosomatic Rehabilitation: Associations with Patient Satisfaction

Abstract: Purpose: Patients' illness and treatment beliefs have been shown to predict health outcomes in many health care settings. However, information about their impact on patient satisfaction is scarce. The aim of this study was to investigate illness-and rehabilitationrelated treatment beliefs and met rehabilitation-related treatment expectations and their relationship with patient satisfaction in psychosomatic rehabilitation. Methods: In a repeated measures study design, patients filled out questionnaires 2 to 3 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
2
6
0
Order By: Relevance
“…On the other hand, compared to other psychosocial factors such as stereotypes and institutional trust affect patient satisfaction by acting on the interaction process, expectations work as a comparative expectation of similar products/services, which are more dependent on the presentation of results (52). When the results are consistent with expectations, the satisfaction level will increase, conversely, if the actual results do not match expectations, it may cause a lower satisfaction level (53). Therefore, doctorpatient interaction, as a process factor, will play a limited role in the impact of patient expectations on patient satisfaction.…”
Section: Patient Expectationmentioning
confidence: 99%
“…On the other hand, compared to other psychosocial factors such as stereotypes and institutional trust affect patient satisfaction by acting on the interaction process, expectations work as a comparative expectation of similar products/services, which are more dependent on the presentation of results (52). When the results are consistent with expectations, the satisfaction level will increase, conversely, if the actual results do not match expectations, it may cause a lower satisfaction level (53). Therefore, doctorpatient interaction, as a process factor, will play a limited role in the impact of patient expectations on patient satisfaction.…”
Section: Patient Expectationmentioning
confidence: 99%
“…In contrast to our hypotheses, neither the dimensions of illness beliefs nor rehabilitation-related treatment beliefs were significant predictors of patient satisfaction. Although previous studies with adult rehabilitation patients have shown the relevance of illness and treatment beliefs for rehabilitation outcomes in general and for patient satisfaction specifically (Glattacker et al, 2013a(Glattacker et al, , 2013b(Glattacker et al, , 2022von der Warth et al, 2022), there are currently no comparable investigations in the field of child and adolescent rehabilitation. One study conducted in the context of mental health services revealed adolescents' positive expectations of treatment as a factor related to satisfaction (Garland et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of adult rehabilitation, patients' illness and treatment beliefs have been shown to be associated with health-related quality of life (HRQOL), attendance at rehabilitation, coping with pain, and psychosocial health at the end of rehabilitation (French et al, 2006;Glattacker et al, 2013aGlattacker et al, , 2013bGlattacker, Giesler, et al, 2018;von der Warth et al, 2022). In addition to illness and treatment beliefs, fulfilled rehabilitation-related treatment expectations in particular were found to predict patient satisfaction in adult psychosomatic rehabilitation (Glattacker et al, 2022). The role of (unmet) expectations for patient satisfaction has been demonstrated in numerous studies with adults in different health care settings, with the fulfillment of expectations being the strongest predictor (Hafkamp et al, 2020;Jackson et al, 2001;Palazzo et al, 2014).…”
mentioning
confidence: 99%
“…When patients experience anxiety or depression, they may exhibit negative attitudes toward communicating with doctors ( Baldwin and Spears, 2019 ). Negative emotions can also influence treatment outcome expectations, resulting in lower satisfaction with treatment effectiveness ( Glattacker et al, 2022 ; Wang et al, 2023 ). Based on these findings, we propose the following hypothesis:…”
Section: Theory and Hypothesesmentioning
confidence: 99%